Long-Term Effect of Adrenalectomy on Cardiovascular Remodeling in Patients With Pheochromocytoma - Majtan, Bohumil; Zelinka, Tomáš; Rosa, Ján; Petrák, Ondrej; Krátká, Zuzana; Štrauch, Branislav; Tuka, Vladimír; Vránková, Alice; Michalský, David; Novák, Kvetoslav; Wichterle, Dan; Widimský, Jirí; et al. (The Journal of clinical endocrinology and metabolism, 2017)
CONTEXT: Catecholamines may contribute to the accumulation of collagen fibers and extracellular matrix in the arterial and myocardial wall due to various mechanisms. Reversibility of this process has not been studied on both structures simultaneously. OBJECTIVE: To clarify the long-term effect of excess normalization of catecholamines on carotid and myocardial wall changes in patients with pheochromocytoma or functional paraganglioma (PHEO) after tumor removal. DESIGN, SETTINGS, AND PATIENTS: Carotid intima-media thickness (IMT) and the left ventricular (LV) mass index were studied in 50 patients with PHEO before tumor removal and 5 years after tumor removal, and in 50 blood pressure- and age-matched essential hypertensive patients before follow-up and after 5 years of follow-up. MAIN OUTCOME MEASURES: Common carotid artery (CCA)-IMT and LV mass indexed to lean body mass (LBM). RESULTS: Elimination of catecholamine excess in the PHEO group resulted in a significant decrease in CCA-IMT and LV mass index from 0.86 ± 0.17 to 0.83 ± 0.18 mm (P < 0.05) and from 3.2 ± 0.9 to 2.9 ± 0.9 g/LBM (P < 0.001), respectively. In contrast, CCA-IMT and LV mass index increased significantly from 0.78 ± 0.14 to 0.81 ± 0.15 mm (P < 0.05) and from 3.1 ± 0.7 to 3.2 ± 0.6 g/LBM (P < 0.05), respectively, in patients with essential hypertension. CONCLUSION: In patients with PHEO, carotid IMT and LV mass index can significantly regress after tumor removal, in contrast to the impairment of these parameters in essential hypertensive patients during the same long-term period.
Keywords: feochromocytom; Pheochromocytoma; Male; nemoci arterie carotis; hypertenze; Essential Hypertension; Carotid Artery Diseases; následné studie; adrenalektomie; Adult; Aged; dospělí; mužské pohlaví; senioři; Adrenal Gland Neoplasms; Hypertension; Ventricular Remodeling; Follow-Up Studies; nádory nadledvin; Carotid Intima-Media Thickness; intimomediální šíře tepenné stěny; hodnocení výsledků zdravotní péče; lidé; ženské pohlaví; Humans; Adrenalectomy; Outcome Assessment, Health Care; Female; esenciální hypertenze; lidé středního věku; remodelace komor; Middle Aged